Analysis of floristic similarity between forest remnants from the upper Paraná river floodplain, Brazil - doi: 10.4025/actascibiolsci.v34i3.8500 - Simone Rodrigues Slusarski; Maria Conceição de Souza (Acta Scientiarum. Biological Sciences, 2012)
The vegetation from the upper Paraná river floodplain is a fragment of Seasonal Semideciduous Forest (SSF) that presents fields, lowlands and extensive areas of pasture along with forest formations. Aiming to accomplish analyses of floristic similarity between riparian forests remnants in this floodplain, an analysis using nine surveys was performed, four on the right bank, two on the left bank and three at an island, including tree species. Sørensen’s (ISs) and Jaccard’s (ISj) similarity coefficients were calculated, and a Correspondence Analysis (CA) was applied to a matrix of presence and absence of species. Thirty-seven families, 80 genera and 110 species were recorded. Among the species, 5.5% were generalist, while 29.1% were exclusive to one survey. The values of ISs and ISj ranged from 31 to 78.4%, and 31 to 64.5%, respectively. The CA grouped the surveys in the right and left banks and the island; the species with the highest positive correlation on axis 1 were the most common in the surveys on the left bank. The obtained results evidenced that floristic surveys constitute important indicatives for evaluations of the vegetation distribution in the floodplain.